2022
DOI: 10.12998/wjcc.v10.i16.5510
|View full text |Cite
|
Sign up to set email alerts
|

Pleural involvement in cryptococcal infection

Abstract: Pleural involvement of cryptococcal infection is uncommon and is more commonly observed in immunocompromised hosts than in immunocompetent ones. Pleural involvement in cryptococcal infections can manifest with or without pleural effusion. The presence of Cryptococcus spp. in the effusion or pleura is required for the diagnosis of cryptococcal pleural infection, which is commonly determined by pleural biopsy, fluid culture, and/or detection of cryptococcal antigen in the pleura or pleural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…In contrast, the positivity rates for pleural fluid culture and serum antigen test were 42%–74% and 63%, respectively 8–10 . Furthermore, the pleural fluid cryptococcal antigen test exhibited a high specificity 8,14 . Serum cryptococcal antigen can serve as an adjunctive screening test, although its sensitivity is not as high as that of pleural fluid cryptococcal antigen 14 .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In contrast, the positivity rates for pleural fluid culture and serum antigen test were 42%–74% and 63%, respectively 8–10 . Furthermore, the pleural fluid cryptococcal antigen test exhibited a high specificity 8,14 . Serum cryptococcal antigen can serve as an adjunctive screening test, although its sensitivity is not as high as that of pleural fluid cryptococcal antigen 14 .…”
Section: Discussionmentioning
confidence: 96%
“…[8][9][10] Furthermore, the pleural fluid cryptococcal antigen test exhibited a high specificity. 8,14 Serum cryptococcal antigen can serve as an adjunctive screening test, although its sensitivity is not as high as that of pleural fluid cryptococcal antigen. 14 However, even though our case showed positive results for pleural fluid cryptococcal antigen and culture, as well as a serum cryptococcal antigen test, these positive results were not consistently reproducible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cryptococcal pleurisy occurs mainly in immunocompromised patients. A review of 76 patients with pulmonary cryptococcosis revealed that five cases involved pleural effusions, with two of these patients being immunocompetent [ 9 ]. Our case is considered noteworthy due to cryptococcal pleuritis in an immunocompetent patient.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of a cryptococcal pleural effusion relies on at least one of the following: positive cryptococcal culture from a pleural fluid or pleural biopsy sample; positive CrAg from pleural fluid or characteristic histopathological findings from a pleural biopsy specimen 12. Histopathological detection of Cryptococcus neoformans is considered the gold standard for diagnosis, and invasive sampling via thoracoscopic or closed pleural biopsy is sometimes necessary, as pleural fluid cultures are frequently negative due to the small number of fungal organisms present in the pleural space 13…”
Section: Discussionmentioning
confidence: 99%